Telaah Kurikulum Sekolah Tahun 2006 Hingga Kurikulum Merdeka Sebuah Perspektif Pandangan Kurikulum Dari Masa Ke Masa - Asep Awaludin; Fina Febriyanti; Trisiani Trisiani; Angela Astrid S.C.A; Elli Erlinawati; Umi Baroroh; Ida Karima; Ngasbun Egar (Pusat Riset dan Inovasi Nasional, 2025)
The development of the education curriculum in Indonesia from 2006 to the emergence of the Merdeka Curriculum reflects the dynamics of change in the education system that adapts to the demands of the times. This article invites us to analyse the curriculum paradigm shift, starting from the 2006 Education Unit Level Curriculum (KTSP), then the 2013 Curriculum, to finally the Merdeka Curriculum. This analysis is carried out by considering philosophical, pedagogical, and social perspectives. Using a qualitative approach and literature study, this research succeeded in identifying the main characteristics of each curriculum, as well as the driving factors behind it and its implications for learning practices. The results of the study show that curriculum changes are not only influenced by advances in science and technology, but also by the need for education that is more flexible, learner-centred, and relevant to global challenges. The Merdeka Curriculum, as a refinement effort, emphasises the importance of differentiated learning, providing autonomy to teachers, and strengthening holistic competencies. This article offers insights into the evolution of curriculum policy in Indonesia and provides recommendations for further development in the context of national education development.